The affecting factors of customer's satisfaction for SMEs / E-commerce websites in Chiang Mai - Marang U. (2014)
At present, Small and Medium Enterprises: SMEs have a very important participation to Thailand's economic mobilization so that the government of Thailand had issued policy of many projects is adoption of E-commerce application instead of buying and selling at the shops' showcase, this is a guideline to enhance a giant leap of development for such category business [15]. However, whether website development in E-commerce system can go successfully or not, it is necessary to know about the factors and the customers' requirement as the principal means so this research had objectives in order to study the satisfaction level of customers group who were using E-commerce websites service to fulfill there needs in various applications such as marketing via internet, design the suitable website structure, design graphic works in order to use it as a guideline in website improvement that responses the customers' requirement most relevantly. The research methodology applied questionnaires distributed among 180 website-customers in Chiang Mai Province, then the collectible data were analyzed, the result appeared that the data responders gave first priority to goods search ability via website while for graphic design requirement, the data responders gave priority about select ability of graphic works on websites which would mostly suit their requirement.